2020
DOI: 10.1186/s12917-020-02598-8
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of and risk factors for Q fever in dairy and slaughterhouse cattle of Jimma town, South Western Ethiopia

Abstract: Background Q fever is a zoonotic disease, caused by Gram negative bacterium C. burnetii, which imparts significant socio-economic burden due to production and reproductive loss (abortion, stillbirth, and infertility) in ruminants and debilitating clinical disease in human populations. While sheep and goats are considered the primary reservoirs of infection to humans, infection can also result from exposure to cattle. Recent studies indicate that in Ethiopia Q fever is a disease of growing publi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
6
14
0
Order By: Relevance
“…Our predictive C. burnetii seroprevalence map indicated that predictive risk was not constant in Jimma town and there were areas, particularly to the east of the town, where the risk of C. burnetii exposure was predicted to be higher. While our previous study demonstrated that cattle in Jimma town were under a high level of C. burnetii exposure [ 15 ], our study expanded current knowledge in that it demonstrated that the east area of the town presented the higher predicted seroprevalence compared to other parts of the town. Our seroprevalence prediction map might help with targeting resources to ensure that communities that are most at risk of Q fever infection to the east of Jimma town are surveyed.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Our predictive C. burnetii seroprevalence map indicated that predictive risk was not constant in Jimma town and there were areas, particularly to the east of the town, where the risk of C. burnetii exposure was predicted to be higher. While our previous study demonstrated that cattle in Jimma town were under a high level of C. burnetii exposure [ 15 ], our study expanded current knowledge in that it demonstrated that the east area of the town presented the higher predicted seroprevalence compared to other parts of the town. Our seroprevalence prediction map might help with targeting resources to ensure that communities that are most at risk of Q fever infection to the east of Jimma town are surveyed.…”
Section: Discussionsupporting
confidence: 68%
“…To estimate the seroprevalence of C. burnetii infection in the Jimma dairy herds, a total of 227 cattle were tested in 25 dairy farms between October 2016 and October 2017 [ 15 ]. Blood samples were collected from the jugular vein from the 227 animals using a vacutainer tube [see reference [ 15 ] for more details]. A total of 14 animals were seropositive for C. burnetii [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations